Individualized medicine and the microbiome in reproductive tract - Braundmeier, Andrea G.; Lenz, Katherine M.; Inman, Kristin S.; Chia, Nicholas; Jeraldo, Patricio; Walther-António, Marina R. S.; Berg Miller, Margret E.; Yang, Fang; Creedon, Douglas J.; Nelson, Heidi; White, Bryan A. (Frontiers in Physiology, 2015)
Humans have evolved along with the millions of microorganisms that populate their bodies. These microbes (1014) outnumber human cells by 10 to 1 and account for 3x 106 genes, more than ten times the 25,000 human genes. This microbial metagenome acts as our “other genome” and like our own genes, is unique to the individual. Recent international efforts such as the Human Microbiome Project (HMP) and the MetaHIT Project have helped catalog these microbial genomes using culture-independent, high-throughput, next-generation sequencing. This manuscript will describe recent efforts to define microbial diversity in the female reproductive tract because of the impact that microbial function has on reproductive efficiency. In this review, we will discuss current evidence that microbial communities are critical for maintaining reproductive health and how perturbations of microbial community structures can impact reproductive health from the aspect of infection, reproductive cyclicity, pregnancy and disease states. Investigations of the human microbiome are propelling interventional strategies from treating medical populations to treating individual patients. In particular, we highlight how understanding and defining microbial community structures in different disease and physiological states heave lead to the discovery of biomarkers and, more importantly, the development and implementation of microbial intervention strategies (probiotics) into modern day medicine. Finally this review will conclude with a literature summary of the effectiveness of microbial intervention strategies that have been implemented in animal and human models of disease and the potential for integrating these microbial intervention strategies into standard clinical practice.